The Entangled Trinity : Quantum Physics and Theology - Simmons, Ernest L. (Theology and the sciences., 2014)
The Doctrine of the Trinity is an exercise in wonder. It is drawn from the wonder of our own existence and the diverse experiences of the divine encountered by the early Christian community. From the earliest days of Christianity, theologians of the church have drawn upon the most sophisticated language and understandings of their time in an attempt to clarify and express that faith. But how should we attempt to articulate that faith today? In this volume, Ernest Simmons engages precisely that question by asking what the current scientific understanding of the natural world might contribute to our reflection upon the relationship of God and the world in a Triune fashion.